High‐performance integrated mid‐infrared filter arrays. Issue 23 (3rd October 2022) - Hakkel, Kaylee D.; van Elst, Don M.J.; Petruzzella, Maurangelo; Ebermann, Martin; Pagliano, Francesco; van Klinken, Anne; Fiore, Andrea
Abstract: A static filter array is developed based on Fabry–Perot cavities operating in the mid‐infrared range from 2 to 4.5 µm, matching the absorption region of several gases relevant for air quality monitoring. The filters include two distributed Bragg reflectors and a high‐index tuning element with varying thickness in between. The filters display high peak transmittance ( > 80 % $>80%$ ) and controllable peak width. The robustness, ease of fabrication and the possibility to tune the optical response to a specific application make the integrated filter arrays suitable for compact sensing systems.